Pembuatan Dan Karakterisasi Komposit Hybrid Serat Pelepah Pisang Kepok (Musa Paradisiaca) Dengan Serat Tandan Kosong Sawit Bermatriks Epoxy - Muhammad Gus Iqbal Al-Pakningi; Warman Fatra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The Empty Fruits Bunches (EFB) is quite good mechanical properties, which it is waste that has not been utilized  and easily broken down. The problem in previous studies was of voids on the surface and in the composite due to the lack of a percentage of the matrix, resulting in a weak interface bond resulting in low mechanical properties. This research uses banana leaf fiber in hybrid with EFB fiber and epoxy matrix then produced by vacuum bagging method. The banana fiber was extracted with a length of 25 cm and EFB fibers a length of 1, 2, and 3 cm and alkaline treatment using 5% NaOH with a soaking time of 2 hours. For The experimental design and variables that have a significant effect on flexural strength, impact resistance, and water absorption, the statistical method Response Surface Methodology (RSM) is used. The results showed that the maximum flexural strength was at running 6 with a value of 209.11 MPa, with a percentage of banana fiber/EFB (50%: 50%) with a percentage of hybrid/matrix fibers (30%: 70%) and 30 mm EFB fiber length. The maximum impact strength is at running 9 with a value of 2.736 Joules, percentage of banana fiber/EFB (60%: 40%) percentage of hybrid/matrix fibers (35%: 65%), and a fiber length of 3 cm EFB. The minimum water absorption is at running 14 with a value of 0.22%, percentage of banana fiber/EFB (60%:40%) with a percentage of hybrid/matrix fibers (25%: 75%), and a length of 1 cm EFB fiber Keywords: Banana Fiber, EFB, Hybrid composites, Vacuum Bagging, Response Surface Methodology (RSM)